Trabalho e desenvolvimento: a realidade rural e a questão social - Sant'ana, Raquel Santos [UNESP] (Cortez Editora Ltda, 2014)
The recognition of the centrality of work in the professional Social Work daily life does not always allow a critical analysis of the social public policy. This article seeks to highlight the materialization of work as the founding axis of the relations established in the current sociability, and it does so by making the Social Work world of labor and policies interlocutors in towns whose main economic activity is the farming of sugar cane. The aim is to provide subsidies to understand the relation among work, social issue and the particularity of the rural in the professional Social Work daily life.

O reconhecimento da centralidade do trabalho no cotidiano profissional do Serviço Social nem sempre permite uma análise crítica da política pública social. Este artigo procura evidenciar a materialização do trabalho como eixo fundante das relações estabelecidas na atual sociabilidade e faz isso por meio da interlocução entre mundo do trabalho e política de assistência social em municípios de pequeno porte cuja principal atividade econômica é a canavicultura. O objetivo é fornecer subsídios para a apreensão da relação entre trabalho, questão social e a particularidade do rural no cotidiano do profissional de Serviço Social.
Work and developmental: the rural reality and the social issue
Keywords: Trabalho; Serviço Social; Questão agrária; Política de assistência social; Work; Social Work; Agrarian issue; Social assistance policy